Association between anorexia of ageing and sarcopenia among Japanese older adults. Issue 5 (19th March 2020) - Tsutsumimoto, Kota; Doi, Takehiko; Nakakubo, Sho; Kim, Minji; Kurita, Satoshi; Ishii, Hideaki; Shimada, Hiroyuki
Abstract: Background: Malnutrition plays an essential role in the mechanism of pathogenesis for sarcopenia. In late life, both food consumption and energy intakes decline. One of key factors for reduced energy intakes is anorexia of ageing. The aim of this study is to examine the association between anorexia of ageing and sarcopenia among community‐dwelling elderly Japanese individuals. Methods: This uses population‐based, cross‐sectional cohort study of elderly Japanese individuals. Anorexia of ageing was assessed via a simplified nutritional appetite questionnaire. Handgrip strength and walking speed were tested, and skeletal muscle mass was assessed using a bio‐impedance analysis device. Subjects with sarcopenia were defined as those who met the criteria of the Asian Working Group for Sarcopenia. The association between anorexia of ageing and sarcopenia was then analysed via multiple regression analysis. Results: In total, 9, 496 elderly Japanese individuals were evaluated (mean age 74.1 ± 5.4 years; male, 47.0%). The prevalence of anorexia of ageing was 9.8% ( n = 927) in the present study. The prevalence of sarcopenia in men was 1.1%, 1.8%, 6.1%, 10.1%, and 21.2% and was 1.6%, 3.3%, 3.6%, 4.8%, and 7.4% in women aged 65–69, 70–74, 75–79, 80–84, and 85 years and older, respectively. The prevalence of anorexia also showed an age‐dependent increase in both sexes ( P < 0.001, respectively). The prevalence of anorexia in men was 8.3%, 6.3%, 9.8%, 13.6%, and 12.9% and was 7.9%, 9.4%, 10.5%, 17.6%, and 17.1% in women aged 65–69, 70–74, 75–79, 80–84, and 85 years and older, respectively. In multivariable logistic regression model adjusted for the covariates except for albumin, anorexia of ageing was independently associated with sarcopenia (OR: 1.45, 95% CI: 1.07 to 1.95; P = 0.015). This significant association remained even after adjusting for all covariates including nutritional status (OR: 1.42, 95% CI: 1.06 to 1.92, P = 0.020). Conclusions: Anorexia of ageing is associated with sarcopenia among Japanese elderly individuals. Further studies are needed to determine whether a causal association exists between anorexia and sarcopenia.